Plan de negocio para la creación de una empresa de consultoría de sistemas de gestión e intermediación de riesgos laborales: Aliados Nacionales en Seguridad, Ambiente y Calidad “ANSAC”. - Lozano, Angela.; Velandia, Sandra. (Corporación Universitaria Minuto de Dios - UNIMINUTO, 2022)
Este documento tiene como propósito presentar el diseño de un plan de negocios para la creación de una empresa que se dedique a prestar servicios de consultoría en el diseño, implementación y seguimiento de sistemas de gestión, intermediación de riesgos laborales, asesorías, capacitación, entre otros, dirigidos a Mipymes en el municipio de Soacha y sus alrededores.

The purpose of this document is to present the design of a business plan for the creation of a company that is dedicated to providing consulting services in the design, implementation and monitoring of management systems, intermediation of occupational risks, consultancies, training, among others, aimed at MSMEs in the municipality of Soacha and its surroundings. It contains a detailed marketing, technical, strategic and financial study, which was carried out taking as a target market the communes 2 and 4 of Soacha, where a survey was designed and applied for the collection of primary information to know the needs of the target market and in which it could be evidenced that there are multiple organizations that still do not comply with the legal requirements in terms of safety and health at work, which represents a business opportunity for National Allies in Safety, Environment and Quality (ANSAC); additionally, it is intended to raise awareness among employers of the importance of the design and implementation of management systems, good management of resources, timely training, among others, which contribute to the improvement of the work environment, well-being and quality of working life, the reduction of absenteeism rates due to illness, the reduction of accident and mortality rates due to occupational accidents, the increase in productivity, positioning and credibility in the market, among many other advantages, in addition to complying with the standards, requirements and procedures of mandatory compliance by companies and contractors in terms of occupational risks.
Realizar un plan de negocios, obteniendo información detallada del mercado potencial para la creación de una empresa de consultoría de sistemas de gestión e intermediación de riesgos laborales en el municipio de Soacha y sus alrededores.
Keywords: Consultoría; Asesoría; Sistema de gestión; Intermediación de riesgos laborales; Seguridad y salud en el trabajo; Mipymes; Consulting; Advisory; Management Systems; Intermediation of labor risk; Occupational Health; Safety Management System